1997
DOI: 10.1126/science.275.5302.983
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Bcl-x L -Bak Peptide Complex: Recognition Between Regulators of Apoptosis

Abstract: Heterodimerization between members of the Bcl-2 family of proteins is a key event in the regulation of programmed cell death. The molecular basis for heterodimer formation was investigated by determination of the solution structure of a complex between the survival protein Bcl-xL and the death-promoting region of the Bcl-2-related protein Bak. The structure and binding affinities of mutant Bak peptides indicate that the Bak peptide adopts an amphipathic alpha helix that interacts with Bcl-xL through hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

56
1,457
1
18

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,401 publications
(1,532 citation statements)
references
References 12 publications
56
1,457
1
18
Order By: Relevance
“…Furthermore, this peptide could inhibit the interaction between wild-type BAK and BCL-X L through competition. 101 These data are compatible with the…”
Section: Figuresupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, this peptide could inhibit the interaction between wild-type BAK and BCL-X L through competition. 101 These data are compatible with the…”
Section: Figuresupporting
confidence: 86%
“…Large arrows refer to amino acid residues in BH3 of BAK which interact with residues (small arrows) in the hydrophobic pocket (BH1-3) of BCL-XL. 101 and cell death regulation, although the contribution of the domains is different within different family members. BH1 to BH3 are conserved in all family members except BAD, whereas BH4 is only conserved in family members with antiapoptotic activity.…”
Section: Figurementioning
confidence: 99%
“…44 Interaction of the disordered BIM, BAD, BMF, BAK, and tBID with several pro-survival BCL-2 family members leads to the formation of an a-helical segment that anchors these BH3-only proteins to the hydrophobic groove of their binding partners. [45][46] In addition to BH3-only proteins shown in Figure 1, pro-survival BCL-2 family members include MCL-1, BFl-1, and BCB-B, all of which are expected to contain long functional IDPRs. 45 Overall, structural and sequence analyses revealed that many pro-apoptotic and pro-survival proteins of the BCL-2 family (which, in their turn, are tightly regulated by various PTMs among other means) are either IDPs or contain functionally important IDPRs.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46] In addition to BH3-only proteins shown in Figure 1, pro-survival BCL-2 family members include MCL-1, BFl-1, and BCB-B, all of which are expected to contain long functional IDPRs. 45 Overall, structural and sequence analyses revealed that many pro-apoptotic and pro-survival proteins of the BCL-2 family (which, in their turn, are tightly regulated by various PTMs among other means) are either IDPs or contain functionally important IDPRs. 46 Furthermore, conformational plasticity and ability to fold upon binding were shown to have a crucial role in multifarious interactions of the BCL-2 family members with their numerous partners.…”
Section: Discussionmentioning
confidence: 99%
“…These two pro-apoptotic proteins contain BH1-3 domains, and have a 3D structure very similar to that of the pro-survival members of the family (Sattler et al, 1997;Suzuki et al, 2000;Moldoveanu et al, 2006). Mice lacking Bax show mild lymphoid hyperplasia and male sterility because of sperm-cell differentiation defects (Knudson et al, 1995).…”
Section: Bax Bak and Bokmentioning
confidence: 99%